"Clinton Defeats Trump" 2016 Polls and the Shadow of 1948. Issue 4 (2nd August 2017) - Lusinchi, Dominic
Abstract: Dominic Lusinchi finds parallels with the past while reviewing a report on last year's presidential election polls